Phytohormone Interaction Modulating Fruit Responses to Photooxidative and Heat Stress on Apple (Malus domestica Borkh.) - Torres, Carolina A.; Sepúlveda, Gloria; Kahlaoui, Besma (Frontiers in Plant Science, 2017)
Sun-related physiological disorders such as sun damage on apples (Malus domestica Borkh) are caused by cumulative photooxidative and heat stress during their growing season triggering morphological, physiological, and biochemical changes in fruit tissues not only while it is on the tree but also after it has been harvested. The objective of the work was to establish the interaction of auxin (indole-3-acetic acid; IAA), abscisic acid (ABA), jasmonic acid (JA), salicylic acid (SA), and ethylene (ET) and its precursor ACC (free and conjugated, MACC) during development of sun-injury-related disorders pre-and postharvest on apples. Peel tissue was extracted from fruit growing under different sun exposures (Non-exposed, NE; Exposed, EX) and with sun injury symptoms (Moderate, Mod). Sampling was carried out every 15 days from 75 days after full bloom (DAFB) until 120 days postharvest in cold storage (1°C, >90%RH). Concentrations of IAA, ABA, JA, SA, were determined using UHPLC mass spectrometry, and ET and ACC (free and conjugated MACC) using gas chromatography. IAA was found not to be related directly to sun injury development, but it decreased 60% in sun exposed tissue, and during fruit development. ABA, JA, SA, and ethylene concentrations were significantly higher (P≤0.05) in Mod tissue, but their concentration, except for ethylene, were not affected by sun exposure. ACC and MACC concentrations increased until 105 DAFB in all sun exposure categories. During post-harvest, ethylene climacteric peak was delayed on EX compared to Mod. ABA and SA concentrations remained stable throughout storage in both tissue. JA dramatically increased postharvest in both EX and Mod tissue, and orchards, confirming its role in low temperature tolerance. The results suggest that ABA, JA, and SA together with ethylene are modulating some of the abiotic stress defense responses on sun-exposed fruit on the tree during photooxidative and heat stress development.